ASPEK HUKUM KELALAIAN MENYETORKAN MODAL DALAM PROSESPENDIRIAN PERSEROAN TERBATAS DAN AKIBAT HUKUMNYA - HUJJATUL MARWIYAH (PREMISE LAW JURNAL, 2015)
A corporation is a legal entity which constitutes capital partnership; it is established based on an agreement to do business activities with initial capital which consists of stocks and has fulfilled all requirements stipulated in law and its administrative regulation. The result of the research shows that by the time a corporation was established, its founders can write a declaration that they have deposited their capital. The problem is that one of them has written a declaration which states that he has deposited his capital; in reality, he does not do it while the corporation has gotten its legalization from the Minister of Law and Human Right. In consequence, his right as a shareholder is postponed until he deposits his capital into the corporation’s savings account. If he fails to do it, the company will withdraw his stocks which mean that the company’s capital is reduced. He is then disqualified since he has breached the agreement in establishing the corporation. The legal consequence is that a founder who feels that he is harmed can make a request for the change of the agreement in establishing the corporation, either with indemnity or not. Legal protection for the other founders who have deposited their capital by the time the corporation is established and legalized can be done, based on the provisions in the contract made by corporation founders and on Law on Corporation. Protection which based on an agreement can be done through the claim for default to the other founders who do not deposit their capital. The ground of this claim is the negligence of the founder himself in carrying out his duties, based on the contract. Protection which is based on Law on Corporation in the form of the right is to bid the stocks beforehand from the founder who does not deposit his capital according to portion of his stocks. Another protection is through RUPS which agrees that the corporation carry out buy-back when the shareholders do not use their right to bid beforehand. Keywords: Corporation, Capital, Declaration of Depositing Capital, Default